Colposcopic evaluation with modified IFCPC 2011 nomenclature and Swede score for diagnosing premalignant lesions of cervix: a comparative study - Arora, Ira; Lal, Prabha; S., Triveni G.; Singh, Smita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer has a long precancerous stage. The early diagnosis in preinvasive stage provides a golden opportunity for prompt intervention to prevent its catastrophic consequences. Through this study we intended to compare the diagnostic accuracy of modified IFCPC 2011 nomenclature and Swede score with respect to gold standard histopathology in colposcopic evaluation of premalignant cervical lesions. Methods: A comparative study was conducted at tertiary care hospital in Delhi, India between January 2021 to June 2022 on 50 women with abnormal Papanicolaou smear (ASCUS, LSIL, ASC-H, HSIL). Scoring of colposcopic lesions was done according to IFCPC nomenclature and Swede’s scoring system. The two colposcopic scores were compared and their statistical association with histological findings were analysed. The collected data was analysed using SPSS version 25. The association of the qualitative variables were analysed using Fischer’s exact test. Agreement was measured by Cohen kappa statistics. Results: Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of modified IFCPC 2011 nomenclature for predicting LSIL and HSIL were 87.50%, 58.82%, 50%, 90.91%, 68% and 100%, 100%, 100%, 100%, 100% respectively. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of swede score for predicting LSIL and HSIL were 87.50%, 41.18%, 41.18%, 87.50%, 56% and 100%, 77.27%, 37.50%, 100%, 80% respectively. Conclusions: Modified IFCPC 2011 nomenclature had better predictive value than swede score in diagnosing both low grade and high grade premalignant lesions of cervix.